In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

The semi-annual oscillation and Antarctic climate. Part 1: influence on near surface temperatures (1957–79) - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
We studied the influence of the semi-annual oscillation (SAO) on near-surface temperatures in Antarctica, using observations of 27 stations that were operational during (part of) the period 1957–79. For the annual cycle of surface pressure, the second harmonic explains 17–36% of the total variance on the Antarctic Plateau, 36–68% along the East Antarctic coast and almost 80% on the west coast of the Peninsula, and decreases further to the north. As a result of the amplification of the wave-3 structure of the circulation around Antarctica, a significant modification of the seasonal cooling is observed at many stations. The magnitude of this modification is largely determined by the strength of the temperature inversion at the surface: the percentage of the variance explained by the second harmonic of the annual temperature cycle is then largest on the Antarctic Plateau (11–18%), followed by the large ice shelves and coastal East Antarctica (6–12%) and stations at or close to the Peninsula (0–5%). A significant coupling between the half-yearly wave in surface pressure and that in surface temperature is found for coastal East Antarctica, which can be directly explained by the changes in meridional circulation brought about by the SAO. We show that the coupling of Antarctic temperatures to the meridional circulation is not only valid on the seasonal time scale of the SAO, but probably also on daily and interannual time scales. This has important implications for the interpretation of time series of Antarctic temperatures, a problem that will be addressed in part 2 of this paper.
Edition: 2004/05/07 Publisher: Cambridge University Press
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

The semi-annual oscillation and Antarctic climate. Part 2: recent changes - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
Following a weakening of the semi-annual oscillation (SAO) since the mid-1970s, the half-yearly pressure wave in the Southern Hemisphere has become less significant. As a result, May/June temperatures have decreased in East Antarctica, which has moderated Antarctic warming. Spectral analysis of 87 years of pressure data at Orcadas suggest that the recent weakening of the SAO is part of the natural variability of the Southern Hemisphere circulation on decadal timescales. We interpret the time series of composite Antarctic temperature in terms of the historical strengthening and weakening of the SAO. If the dominant oscillations that occurred in the past prove to be persistent, an accelerated East Antarctic warming trend is expected for the coming decades. There are indications that the strength of the SAO is linked to the Southern Oscillation, in the sense that warm phases of the Southern Oscillation coincide with strong westerlies, a weakly developed SAO and below-average temperatures in East Antarctica. Temperatures on the west coast of the Antarctic Peninsula show strongly deviant patterns, which can not be explained by the same mechanism that applies to East Antarctica.
Edition: 2004/05/07 Publisher: Cambridge University Press
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Climatological tables for Norway Station (70°30' S, 2°32' W) - Vinje, Torgny E (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; klimatologi